2012
DOI: 10.1016/j.ijpharm.2012.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous solid dispersion enhances permeation of poorly soluble ABT-102: True supersaturation vs. apparent solubility enhancement

Abstract: Amorphous solid dispersions (ASDs) represent a promising formulation approach for poorly soluble drugs. We explored the formulation-related impact of ASDs on permeation rate, apparent solubility and molecular solubility of the poorly soluble drug ABT-102. The influence of fasted state simulated intestinal fluid (FaSSIF) as dispersion medium was also studied. ASDs were prepared by hot-melt extrusion. Permeation rate was assessed by the Caco-2 transwell assay. Cell viability and barrier integrity were assured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(74 citation statements)
references
References 24 publications
1
72
0
1
Order By: Relevance
“…10 Supersaturatable dosage forms improve the solubility and oral bioavailability of water-insoluble drugs, and are now being widely explored in the pharmaceutical industry. [11][12][13][14][15] Amorphous solid dispersion and lipid-based formulations (eg, the supersaturatable self-microemulsifying drug delivery system) containing polymeric precipitation inhibitors are regarded as supersaturatable formulations. The supersaturated state is a thermodynamically unstable amorphous form and eventually reverts to a stable state because of drug precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…10 Supersaturatable dosage forms improve the solubility and oral bioavailability of water-insoluble drugs, and are now being widely explored in the pharmaceutical industry. [11][12][13][14][15] Amorphous solid dispersion and lipid-based formulations (eg, the supersaturatable self-microemulsifying drug delivery system) containing polymeric precipitation inhibitors are regarded as supersaturatable formulations. The supersaturated state is a thermodynamically unstable amorphous form and eventually reverts to a stable state because of drug precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that enhanced apparent solubility, which is because of micellarization or complexation, does not induce an enhanced permeation rate of a poorly soluble drug in vitro. 26,[40][41][42][43][44] The solubility-permeability interplay cannot be ignored when using solubility-enabling formulations. 45,46 As mentioned earlier, we can draw a conclusion that increasing drug solubility utilizing pharmaceutical techniques does not necessarily lead to improved bioavailability.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…This result is consistent with the previous literature. 43,44 Compared to GM solubility in water (1.6 µg/mL), the solubility of an optimized GMME formulation increased up to 340 times (544.6±4.91 µg/mL). Meanwhile, a noticeable enhancement in GM dissolution was observed in the GM-MU complex -the solubility of GM was found to increase up to 24,000 times.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…The angle range was chosen for the indication of crystallinity of ABT-102, because a previous study showed that crystalline ABT-102 showed its biggest reflex in that range. 13 FT-IR studies of the dried precipitate were done to determine the ingredients of the amorphous microparticles. Figure 8 presents the spectra of the single compounds and of the precipitate (microparticles).…”
Section: Analysis Of the Precipitatementioning
confidence: 99%